Estomatitis herpética en pacientes inmunocomprometidos. revisión bibliográfica - Rivera Ortiz, Stalin Joseph (2025)
Introduction: Herpetic stomatitis is an acute viral pathology that can affect both pediatric and adult populations. Also, immunocompromised patients, present a challenge for dental professionals due to the severity of symptoms. Objective was to analyze the characterization of herpetic stomatitis in immunocompromised patients through a literature review. Methodology focused on a systematic review of the literature using a documentary analysis approach following the PRISMA style. Scientific articles published between 2019 and 2024 were searched on Google Scholar, PubMed, and Elsevier, applying predefined inclusion and exclusion criteria to select relevant studies. Results, 535 initial articles were obtained, and 16 articles were selected after a rigorous process of removing duplicates and reviewing titles, abstracts, and full texts. Conclusion: that herpetic stomatitis in immunocompromised patients is characterized by greater persistence, recurrence, and duration of lesions due to the immune system's inability to control viral replication. This highlights the need for careful dental surveillance, including fundamental oral hygiene measures to prevent complications, and combining therapeutic modalities to improve disease control and patient quality of life.